Minat Masyarakat Terhadap Pasar Modal Syariah - Melani Musran (Department of Islamic Accounting, Faculty of Islamic Economics and Business, IAIN Sultan Amai Gorontalo, 2021)
The role of an investor in the world of capital markets is needed. This is an effort to control economic stability that occurs due to financial crises throughout the country's economy. In the capital market economy plays an active role as one of the supporting indicators of the economy. Where the capital market has two functions, namely first as a means of business funding, secondly the capital market becomes a means for the public to invest in the capital market. The Capital Market is also an effort to support policies made by the government. Over time, now we know the term Islamic capital market which is a form of cooperative effort between PT. Indonesia Stock Exchange and MUI DSN. The Islamic capital market aims to be an investment choice for customers who want to invest their wealth in the field of sharia, both Muslim and non-Muslim investors. This is not a young thing for potential investors who will go directly to the world of Islamic capital markets. It requires sufficient expertise and knowledge about investment. As a form of business in investor development, it is necessary to educate the public about the capital market, this is the reason for the author to answer the problem using an empirical approach in which data is directly obtained from sources and then processed using qualitative research.